Assessment of the Pediatric Nurses’ Knowledge about the Nosocomial Infection in the Neonatal Intensive Care Unit of Baghdad Pediatric Teaching Hospitals - Adra’a Hussein shauq (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To assess the pediatric nurses’ knowledge about the nosocomial infection owl), and to fud out the relatiouships between their knowledge about the nosocomial infection and demographic data. Methodology: A descriptive study was carried out at neonatal intensive care units OVICUs) of Baghdad Pediatric Teaching Hospitals. It was started from the end of April to the end of October, 2008. A purposive sample of (28) pediatric nurses were selected. The data were collected by self-administered questiormaire. The validity of the questionnaire was detemined through a panel of experts, while its reliability was detemined through the pilot study. The data were analyzed by descriptive and inferential statistics through the package SPSS version (10.0). Results: The findings indicated that the pediatric nurses who work at neonatal intensive care units have an inadequate level of knowledge about all aspects of the NI. Nurses’ age, educational level, and their years of employment in the general hospitals, pediatric hospitals, and NICU have a significant association with their knowledge. However, nurses’ educational courses and updating knowledge about the NI have no association with their knowledge. Recommendation: The study recommends that all the pediatnc nurses should be exposed to educational courses to raise their awareness about the NI. Encourage transmission barriers use (hand hygiene, personal protective equipment), especially the most important and simple procedures to reduce the NI "hand hygiene". Further studies should include other nurses in all hospitals, especially in the ICUs.